REVISING THE INFLUENCE OF AGING ON THE FOOD SHOPPING ENVIRONMENT. (11th November 2018) - Zniva, R; Lienbacher, E; Weber, D
Abstract: According to gerontological literature personal and environmental resources contribute to successful aging. The study at hand investigates this person-environment relationship in food retailing. Previous studies created a strong body of knowledge stating that the quality of life of older consumers can be additionally improved by adapting retail environments to personal needs. However, in practice few of these adapted retail concepts cater successfully to older consumers. Therefore, the research project aims to analyze this discrepancy between research results and their implementation in practice. We conducted two studies using a mixed methods design. The first qualitative study investigates the influence of social environments with different age structures on the food retail environment and vice versa. Using a case study design, we conducted 69 depth interviews and 50 observations of food shopping trips in three differently aged social environments (a retirement community, a college town, and a city) and analyzed data using content analysis. In the second quantitative study we investigated the influence of biological, psychological, and social aspects of aging on the perception of food retail environments investigating a sample of 913 younger and older consumers with a structural equation model. Our results show, in line with the SPOT approach in environmental gerontology, that functions of maintenance and support are getting more important when growing old. Furthermore, the need for adaptions is driven by health status and the experience of life events. Based on our results, retailers need to do less but more universally designed adaptions to address older consumers' needs.